Hubungan kualitas udara hasil pembakaran avtur dengan gangguan fungsi paru pekerja di bandara Supadio Pontianak - Zuzun Nazila; Adi Heru Sutomo (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Air quality of aviation building and disturbed lung function of workers in Supadio Airport PontianakPurposeThis study aimed to determine the relationship of air quality aviation fuel combustion products with impaired lung function in workers in Pontianak Supadio International Airport.MethodsThis research was an observational study using a cross-sectional approach involving 60 people. Sampling technique used total sampling. The statistical analysis used Fisher exact and logistic regression tests, with significance level of p < 0.05 and 95% confidence interval and odds ratios. ResultsBased on bivariate analysis from 36 samples the results were: NO2 variable (p = 0.04), SO2 (p = 0.15), dust (p = 0.25), age (p = 0.20), working period (p = 0.08), nutritional status (p = 0.09), and smoking habits (p = 0.03). ConclusionThere is significant correlation between the variables of NO2 and smoking habits with impaired lung function, while the variables: SO2, dust, age, working period and nutritional status had no significant correlation with lung function disorders.